Estimation of Market Values of Football Players through Artificial Neural Network: A Model Study from the Turkish Super League - Tugbay Inan; Levent Cavas (Applied Artificial Intelligence, 2021)
Artificial intelligence (AI) has been widely affecting our lives in many ways for the last ten years. Potential applications of AI are currently being used in many sectors. However, the usage of AI has been very limited in sports science compared to the other sectors. In this study, we developed an artificial neural network model to estimate the market values of the players in the Turkish Super Football League. While the market value was selected as an output, the input values were: minutes played; goals scored; xG: assists; xA; defensive duels won %; tackle success %; shots on target %; Short-middle pass accuracy %; long pass accuracy %; and accuracy of passes to penalty area. After creating a neural network based on the input-output values with high training, validation and testing statistical values, input values were computed with the neural network created and then the output values were estimated. In conclusion, an artificial neural network is becoming one of the important modeling methods in all areas of life. Although the application of artificial neural networks is very limited in sports science, it is one of the suitable science disciplines where there is a lot of statistical data. The methodology proposed in this paper can also be used for talent selection in football. Moreover, it may help stop criticism by TV sports programmes and newspapers because market value estimation is based on fair performance parameters. Further studies are strongly recommended, not only for football but also for other sports disciplines.